2023
DOI: 10.1007/s00284-023-03279-z
|View full text |Cite
|
Sign up to set email alerts
|

Retrospect of the Two-Year Debate: What Fuels the Evolution of SARS-CoV-2: RNA Editing or Replication Error?

Abstract: Mutation is one of the mechanisms of the evolutionary divergence of an organism. Under this global COVID-19 pandemic, the fast evolution of SARS-CoV-2 became one of the most worrying issues. Some researchers believed that the hosts’ RNA deamination systems (APOBECs and ADARs) are the major source of mutations and have driven the evolution of SARS-CoV-2. However, apart from RNA editing, the RDRP (RNA-dependent RNA polymerase)-mediated replication errors may also contribute to the mutation of SARS-CoV-2 (just li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Each titer was obtained by logistic regression of the average of 3 replicas and is the geometric mean value of two independent experiments. 3 Protein concentration of the preparation 003 able to reduce 50% of the lytic plaques.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each titer was obtained by logistic regression of the average of 3 replicas and is the geometric mean value of two independent experiments. 3 Protein concentration of the preparation 003 able to reduce 50% of the lytic plaques.…”
Section: Resultsmentioning
confidence: 99%
“…2 Phosphate Buffer Saline (PBS). 3 Preparation 002 is the product of the bleeding at 3 weeks plus a remnant of preparation 001. 4 The horses were immunized with 500 µg of RBD in a two-day interval.…”
Section: Equine Anti-rbd Hyperimmune Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADAR family members (ADAR1-3) deaminate adenines residing in double-stranded RNA (dsRNA), converting them to inosines (A-to-I) [14], while APOBEC family members (APOBEC1-2, 3A-H, 4, and AID) deaminate cytosine into uracil (C-to-U) on single-stranded RNA (ssRNA) [15,16]. The relative mutational impact between RdRp (RNA-dependent RNA polymerase), which introduces errors during replication, and RNA editing enzymes, remains unclear [17][18][19]. Recent studies revealed an enrichment of C-to-U substitutions and, to a lesser extent, A-to-G substitutions in the SARS-CoV-2 genome, offering evidence for RNA editing by APOBEC and potentially by ADAR enzymes [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%